Quantifying the psychosocial impact of a weekend retreat on adolescent and young adult (AYA) oncology patients. Issue 6 (6th July 2020) - Antonetti, Callah; Stromberg, Sarah E.; Costello, Aimee; Faith, Melissa A.; Shaw, Peter H.
Abstract: Objective: This study aimed to determine if AYA oncology patients experienced a quantifiable improvement in psychosocial outcomes after attending a weekend retreat with their peers. Methods: AYA oncology patients attended a weekend retreat. They completed the Functional Assessment of Cancer Therapy – General (FACT-G) before, 1 month after, and 6 months after the weekend retreat. Controls were age-matched oncology patients who did not attend the retreat. Findings: Retreat participants' scores did not significantly change over time; however, retreat participants' scores at 1-month follow-up were significantly higher than control group scores. Conclusions: AYA oncology patients may experience transient improvement in psychological well-being after attending a retreat, but benefits may not be durable. Work remains needed to examine the impact of retreat attendance on specific aspects of psychosocial well-being. Implications for psychosocial oncology: Work is needed to decrease perceived attendance barriers for AYA oncology patients who have a low quality of life. Future retreat planners may consider modifying retreat activities and consider alternative retreat locations that appeal to campers with limited mobility, chronic pain, and/or other quality of life limitations. Additional study is needed to determine whether brief overnight or weekend retreats can be as effective as week-long camps in enhancing oncology patients' quality of life. Future researchers should compare changes in weekend retreat attendees' quality of life to changes in quality of life for a control group (e.g., via a waitlist control study design).